Metabolite Profiling of Balinese Grape (Vitis vinifera L. Var. Alphonso Lavallee) Kombucha: GC-MS Analysis - Damayanti, Ida Ayu Manik; Wulansari, Nadya Treesna; Dharmapatni, Ni Wayan Kesari; Antari, Ni Wayan Sukma (Sciences of Phytochemistry, 2026)
Balinese grape (Vitis vinifera L. var. Alphonso Lavallee) is a local grape variety containing various phytochemical constituents. Fermentation into kombucha using a symbiotic culture of bacteria and yeast (SCOBY) may alter the chemical composition of the substrate through microbial metabolic activity. This study aimed to characterize the metabolite profile of Balinese grape kombucha using Gas Chromatography-Mass Spectrometry (GC-MS). GC-MS analysis detected several chemical constituents, including fatty acid esters, alkaloids, and terpenoid hydrocarbons. The major compounds identified based on mass spectral library matching were 9-Octadecenoic acid methyl ester (E)-, acetic acid n-octadecyl ester, caffeine, and 2,6,10,14,18,22-tetracosahexaene, 2,6,10,15,19,23-hexamethyl-, (all-E)-. These results describe the metabolite profile detected in the fermented sample and indicate changes in chemical composition following kombucha fermentation. The findings provide preliminary information on the chemical constituents of Balinese grape kombucha and may serve as a basis for further studies involving comparative analyses with unfermented substrates and confirmation of compound identities using complementary analytical approaches.